General self-efficacy and self-directed learning readiness among nursing internship students: A Cross-Sectional Study - Tiwi Sudyasih; Diyah Candra Anita (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: Self-directed learning readiness (SDLR) is a core competency in nursing education, particularly during internship programs that require autonomy, accountability, and clinical adaptability. General Self-Efficacy (GSE) has been theoretically associated with motivation, persistence, and self-regulation, which are central to self-directed learning. However, empirical evidence regarding the relationship between GSE and SDLR in structured internship contexts remains inconclusive. This study aimed to examine the association between GSE and SDLR among nursing students undertaking internship projects. Research Methodology: A cross-sectional analytic study was conducted involving 295 nursing internship students at Universitas Aisyiyah Yogyakarta, Indonesia, selected through total sampling. Data were collected using validated General Self-Efficacy (GSE) and Self-Directed Learning Readiness (SDLR) scales. Descriptive statistics were used to summarize respondent characteristics. Bivariate analysis was performed using the chi-square test, and odds ratios (OR) with 95% confidence intervals (CI) were calculated. Multivariate logistic regression analysis was conducted to control for sex. Statistical significance was set at p < 0.05. Results: Most respondents demonstrated high GSE (69.8%) and high SDLR (86.4%). Students with high GSE were more likely to report high SDLR compared to those with moderate GSE (OR = 1.468; 95% CI: 0.732–2.940; p = 0.277). After adjustment for sex, the association remained non-significant (AOR = 1.420; 95% CI: 0.701–2.875; p = 0.320). Although a positive directional trend was observed, the effect size was weak and did not reach statistical significance. Conclusion: General self-efficacy was not an independent predictor of self-directed learning readiness in this internship context. These findings suggest that a combination of individual psychological factors and structured educational support influences SDLR. Nursing education programs should integrate mentorship, scaffolded autonomy, and training in problem-solving and self-management to strengthen students’ readiness for professional practice.